Who’s afraid of Kaassassuk? Writing as a tool in coping with changing cosmology - Sonne, Birgitte (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2010)
Education, literacy, and art were technologies used by Greenlanders in adapting to and coping with changes brought about by colonial impacts from Denmark. Stories orally transmitted through the ages were among the first texts to be written by Greenlanders. This article focuses on changes in symbolic meanings of the environmental setting in the pan-Inuit myth about the maltreated orphan Kaassassuk who became a strong man and took a terrible revenge. Beginning with the traditional pan-Inuit and Greenland variants, the analysis ends up with Hans Lynge’s play Kâgssagssuk, staged in 1966. Traditionally, the symbolism of the natural forces underscored Kaassassuk’s brutal character, but later it structured the literary composition of his story and changed him into a re-socialised individual. In Lynge’s play, the natural forces even gave way to contemporary moral and psychological considerations during the political upheaval leading to Greenland’s Home Rule.